Tinjauan terhadap Tindak Pidana Dalam Praktek Kedokteran - Gunawan Jatmiko (Law Faculty of Universitas Bandar Lampung, 2006)
Relationship between doctor and thisÂ patient sometimes cause law problemalic. This problem is become ifÂ the action of doctor cause invalid and died. So doclor can be procecuted in cri minal procces. The problem in lhis research are how the type of crime in practice for doctor? How the proofing the crime in practice for doclor ? Conclusion pf this research there are two type crime in practice for doctor First crime that can be clasificated on yuidicial malpractic andÂ second cri me that can be clasificated on ethical malpractice. To proofing crime inÂ practice for doctor must any evidence that can direct to yuridice malpractice or Â eticmallpractic.